2020
DOI: 10.1007/s00405-020-05838-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical nodal management in hypopharyngeal and laryngeal cancer

Abstract: Objective The aim of this study is to compare pre-therapeutic staging of the loco-regional lymphatic basin and subsequent surgical management in cN0 versus cN+ hypopharyngeal and laryngeal cancer patients. Methods We analyzed all hypopharyngeal and laryngeal carcinoma patients treated surgically at a single quaternary medical care and cancer center between 2004 and 2014. We established two groups for patients who underwent neck dissection comparing patients with a low LNR (lymph node ratio) to one with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This case underscores the strengths of our model in predicting neck lymph node status, thereby aiding clinical decision-making. The study indicates that current clinical assessment methods are no longer sufficient to accommodate the complex needs of patients ( 12 , 13 ). In contrast, our model has the potential to prevent both over-treatment and under-treatment resulting from limited assessments.…”
Section: Resultsmentioning
confidence: 95%
“…This case underscores the strengths of our model in predicting neck lymph node status, thereby aiding clinical decision-making. The study indicates that current clinical assessment methods are no longer sufficient to accommodate the complex needs of patients ( 12 , 13 ). In contrast, our model has the potential to prevent both over-treatment and under-treatment resulting from limited assessments.…”
Section: Resultsmentioning
confidence: 95%
“…This fact should not be underestimated and survival outcome should not be jeopardized when considering surgical refinement in terms of reducing the extent of dissection. In contrast, several previous retrospective studies showed no significant influence of elective neck dissection (END) on survival in advanced laryngeal cancers (Ketterer et al 2020;Shi et al 2019;Kennedy et al 2017;Djordjevic et al 2016;Canis et al 2012). For salvage TL cases, END is not generally recommended, because, although it reduces the rate of regional recurrence, it does not provide a survival benefit as stated in a recent meta-analysis (Davies-Husband et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lymph nodes metastasis has widely been described as one of the main prognostic factors of laryngeal cancer and is associated with an increased risk of regional recurrence. 25 , 26 , 27 , 28 Different studies have investigated the importance of ND including an adequate number of lymph nodes in improving regional control and survival rates, however no consensus exists on superiority of bilateral versus unilateral ND for glottic LALC yet. 25 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%